Esthetic rehabilitation of crowded and protruded anterior dentition - Cecilia G. J. lunardhi; Eric Priyo Prasetyo (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Recent trends put estheticrehabilitationas a demandingtreatmentin order to correct malpositionedanteriordentition. This is enhanced by the patient’s background, especially careers that require prime appearance for the public. Purpose: To describe that even though there are many treatment alternatives and procedures, esthetic rehabilitation on crowded and protruded anterior dentition using endodontic treatment, cast posts and all ceramic crowns, can improve patient’s appearance. Case: This article presents a case report on esthetic rehabilitation of crowded and protruded anterior dentition. Treatment was done due to patient’s refusal in receiving orthodontic treatment. The patient requested esthetic rehabilitation as an expectation for faster and instant esthetic result. Case management: Endodontic treatment was done to the involved dentition prior to the final restoration. Cast posts and all ceramic crowns were used as final restoration to correct the crowded and protruded anterior teeth. Conclusion: Esthetic rehabilitation can be done successfully on crowded and protruded anterior dentition. Instant result could be achieved by this treatment. This is supported by the fact that dentists should be aware of not only choosing the right treatment and materials but also patient’s expectations and conditions.